Comparison of Coal Reserve Estimation Methods, Case Study PT. Bukit Asam Area, South Sumatra, Indonesia - Taufiq Muhammad Wijayanto; Wahyu Wilopo; I Gde Budi Indrawan; Sunarko Sunarko (Journal of Applied Geology, 2021)
The calculation of coal reserves is influenced by the dimensions or size of the coal deposit. There are several types of coal reserve calculation methods, and the use of these methods is adjusted to existing geological conditions. Each method will produce a different amount of coal reserves, although the location is the same. Besides, the amount of coal mining that can be produced is primarily determined by the mine design, especially the optimal slope as a basis for mining pits in the coal extraction. This research aims to estimate coal reserves based on existing pit designs using a variety of methods. Data on coal thickness and topography are used as the basis for reserves estimation. Coal reserve estimation is conducted in several methods: nearest neighbor point (NNP), inverse distance weighted (IDW), and kriging using Surfer 13 software. The results of the reserves estimation indicate that kriging is the best method by providing the smallest error value with an RMSE value of 0.67 and coal reserves of 27,801,543 tons.